Hypoalbuminaemia, Not Biologic Exposure, Is Associated with Postoperative Complications in Crohn's Disease Patients Undergoing Ileocolic Resection. (3rd January 2021) - Shah, Ravi S; Bachour, Salam; Jia, Xue; Holubar, Stefan D; Hull, Tracy L; Achkar, Jean-Paul; Philpott, Jessica; Qazi, Taha; Rieder, Florian; Cohen, Benjamin L; Regueiro, Miguel D; Lightner, Amy L; et al.
Abstract: Background: There are limited data on the postoperative outcomes in Crohn's disease patients exposed to preoperative ustekinumab or vedolizumab. We hypothesised that preoperative biologic use in Crohn's disease is not associated with postoperative complications after ileocolic resection. Methods: Crohn's disease patients who underwent ileocolic resection over 2009–2019 were identified at a large regional health system. Preoperative biologic use within 12 weeks of surgery was categorised as no biologic, anti-tumour necrosis factor, vedolizumab, or ustekinumab. The primary endpoint was 90-day intra-abdominal septic complication. Risk factors included preoperative medical therapies, demographics, disease characteristics, laboratory values, and surgical approach. Regression models assessed the association of biologic use with intra-abdominal septic complication. Results: A total of 815 Crohn's disease patients who underwent an ileocolic resection were included [62% no biologic, 31.4% anti-tumour necrosis factor, 3.9% vedolizumab, 2.6% ustekinumab]. Primary anastomosis was performed in 85.9% of patients [side-to-side 48.8%, end-to-side 26%, end-to-end 25%] in primarily a stapled [77.2%] manner. Minimally invasive approach was used in 41.4%. The 90-day postoperative intra-abdominal sepsis rate of 810 patients was 12%, abscess rate was 9.6%, and anastomotic leak rate was 3.2%. Multivariable regression modelling controlling for confounding variables demonstrated that preoperative biologic use with anti-tumour necrosis factor [ p = 0.21], vedolizumab [ p = 0.17], or ustekinumab [ p = 0.52] was not significantly associated with intra-abdominal septic complication. Preoperative albumin < 3.5 g/dl was independently associated with intra-abdominal septic complication (odds ratio [OR] 1.76 [1.03, 3.01]). Conclusions: In Crohn's disease patients undergoing ileocolic resection, preoperative biologics are not associated with 90-day postoperative intra-abdominal septic complication. Preoperative biologic exposure should not delay necessary surgery.